Numerical and experimental study of axial splitting of circular tubular structures. (August 2016) - Rouzegar, Jafar; Karimi, Mohammad
Abstract: Among the different energy absorption mechanisms, axial splitting/curling is known as an efficient method due to its large stroke to length ratio. This paper presents a finite element model for numerical simulation of splitting of circular brazen tubes. Surface-based cohesive technique is employed for modeling fracture and cracks growth. The required material parameters are extracted from stress-strain diagram of simple tensile test. Some experimental tests were performed to validate the numerical results. For implementation of experimental procedure, the specimens were prepared by cutting the commercial brazen tube and some edge notches were created on one end side of tubes. The specimens were axially compressed between a rigid plate on top and a conical die at the bottom using Zwick universal testing machine. Good agreements were found between numerical simulations and experimental tests. The effects of several parameters such as number and length of initial notches, diameters and thickness of tubes and vertex angle of dies on energy absorption capacity of specimens are investigated, numerically. Highlights: This paper presents a FE model for simulation of splitting of brazen tubes. Surface-based cohesive technique is employed for modeling cracks growth. Experimental test was performed to validate the numerical results. Effects of different geometrical parameters are studied.